Biophilic Cities for an Urban Century. Why nature is essential for the success of cities. - McDonald, Robert; Beatley, Timothy (Palgrave Macmillan, 2020)
This book argues that, paradoxically, at their moment of triumph and fastest growth, cities need nature more than ever. Only if our urban world is full of biophilic cities will the coming urban century truly succeed. Cities are quintessentially human, the perfect forum for interaction, and we are entering what could justly be called the urban century, the fastest period of urban growth in human history. Yet a growing body of scientific literature shows that the constant interaction, the hyper-connectedness, of cities leads to an urban psychological penalty. Nature in cities can be solution to this dilemma, allowing us to have all the benefits of our urban, connected world yet also have that urban home be a place where humanity can thrive.
Keywords: Stadtentwicklung; Stadtökologie; Stadtnatur; Stadtgrün; Klimawandel; Gesundheit; Lebensqualität; Natürliche Umwelt; Biophiles Design; New Urban Agenda